2011
DOI: 10.1186/1471-2148-11-155
|View full text |Cite
|
Sign up to set email alerts
|

Scaling properties of protein family phylogenies

Abstract: BackgroundOne of the classical questions in evolutionary biology is how evolutionary processes are coupled at the gene and species level. With this motivation, we compare the topological properties (mainly the depth scaling, as a characterization of balance) of a large set of protein phylogenies with those of a set of species phylogenies.ResultsThe comparative analysis between protein and species phylogenies shows that both sets of phylogenies share a remarkably similar scaling behavior, suggesting the univers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 66 publications
6
16
0
Order By: Relevance
“…Ultimately, this process is shaping the diversity of life on Earth. Our findings on evolutionary relatedness and the diversification of B1-subfamily members support the universal branching rule (Herrada et al 2011(Herrada et al , 2008, and we assume that this rule applies everywhere from gene families to protein families, and finally, within the continuous process of speciation. Our analysis impressively suggests that evolutionary relatedness occurs during the branching process.…”
Section: Resultssupporting
confidence: 76%
“…Ultimately, this process is shaping the diversity of life on Earth. Our findings on evolutionary relatedness and the diversification of B1-subfamily members support the universal branching rule (Herrada et al 2011(Herrada et al , 2008, and we assume that this rule applies everywhere from gene families to protein families, and finally, within the continuous process of speciation. Our analysis impressively suggests that evolutionary relatedness occurs during the branching process.…”
Section: Resultssupporting
confidence: 76%
“…An asymptotic behavior as is found to correspond to a well defined value of the parameter in the beta-splitting model and it is associated to a great variety of real phylogenetic tree [5]. Moreover, in some recent analysis [13], [8], authors found the same asymptotic behavior (respectively and ) for the mean topological distance and the mean depth when looking at the scaling laws of all the trees in the PANDIT [46] and TreeBASE [47] databases. It should be noted that logarithmic exponent can greatly vary in these cases and the authors of [8] mention that a power law with fits TreeBASE data equally well [48] while for larger tree sizes as those contained in PANDIT, the seems more accurate.…”
Section: Methodsmentioning
confidence: 99%
“…We have calculated [11,12] the depth d for all trees (and subtrees) in the phylogenetic databases TreeBASE (containing species phylogenies [16]) and PANDIT (protein phylogenies [17]). The result in Figure 1(a) suggests that the average depth grows with the number of tips as…”
Section: Tree Shape and Depthmentioning
confidence: 99%
“…Evolutionary histories and genealogies are naturally represented as trees. Each branching point represents an ancestral relationship in a population or an event of diversification on sets of languages [8], species [9][10][11][12][13] or socio-cultural innovations [14]. Based on genetic information, modern computational biology has inferred thousands of trees, socalled phylogenies [15], depicting the evolutionary relationships between sets of species, from bacteria to mammals [16].…”
Section: Introductionmentioning
confidence: 99%